Aplicação de Critérios Ergonômicos de Usabilidade em Sistemas Ubíquos - Milczuk, Samuel Stephan (2022)
With the rapid advance in computing and the advent of mobile technologies and ubiquitous computing, new devices have emerged with different structures from traditional computers, with specific interfaces. These kinds of interfaces raise doubts about the efficiency of classic usability evaluation methods regarding aspects of these interfaces that did not exist at the time they were developed, such as the Ergonomic Usability Criteria proposed by Dominique Scapin and Christian Bastien in 1993. This research analyzes how the Ergonomic Criteria adapt to non-conventional contexts, such as ubiquitous computing, through a bibliographic survey and evaluations carried out in different contexts. Results revealed that the number of published works using the Ergonomic Criteria to evaluate usability in ubiquitous contexts is small. Existing research usually considered users’ physical/ergonomic aspects concerning their movement and exhaustion. Another problem concerns the stimuli users receive and their attention at the time of use. These problems were confirmed by carrying out the evaluations, which also revealed new problems. Finally, adjustments were suggested to the criteria, forming a new list to best fit ubiquitous contexts.